A Conceptual Framework for the Impact of Junior Achievement-Company Program on School Students' Entrepreneurial Intention in Oman - Al Harrasi, Zahran Abdulwahad; Ali, Mass Hareeza (Advances in Social Sciences Research Journal, 2025)
The fundamental purpose of this research is to provide a conceptual framework on the impact of the Company Program on students' entrepreneurial intention as it has been intended to stimulate students' motivation to be engaged in self-employment in the future. This research was motivated by the significance of effective entrepreneurship education in fostering students’ intention into the world of business. Thus, entrepreneurship education in the school system is becoming a necessity. The Company Program is an entrepreneurship education initiative designed by Junior Achievement Worldwide to provide students an opportunity for experiential learning to start and manage their own mini companies. The present literature reveals that reliable entrepreneurship education has a vivid role on fostering students’ intention towards entrepreneurship. This paper adopts Ajzen’s Theory of Planned Behavior which approves three antecedents of attitudes, subjective norms, and perceived behavioral control to determine individuals’ intentions. Therefore, this research proposes that the Company Program has a positive impact on students' entrepreneurial intention in the Omani schools including the three determinants of attitudes, subjective norms, and perceived behavioral control.